Derivation of Thyroid Follicular Cells From Pluripotent Stem Cells: Insights From Development and Implications for Regenerative Medicine - Posabella, Alberto; Alber, Andrea B.; Undeutsch, Hendrik J.; Droeser, Raoul A.; Hollenberg, Anthony N.; Ikonomou, Laertis; Kotton, Darrell N. (Frontiers in Endocrinology, 2021)
Stem cell-based therapies to reconstitute in vivo organ function hold great promise for future clinical applications to a variety of diseases. Hypothyroidism resulting from congenital lack of functional thyrocytes, surgical tissue removal, or gland ablation, represents a particularly attractive endocrine disease target that may be conceivably cured by transplantation of long-lived functional thyroid progenitors or mature follicular epithelial cells, provided a source of autologous cells can be generated and a variety of technical or biological challenges can be surmounted. Here we review the emerging literature indicating that thyroid follicular epithelial cells can now be engineered in vitro from the pluripotent stem cells (PSCs) of mice, normal humans, or patients with congenital hypothyroidism. We review the in vivo embryonic development of the thyroid gland and explain how emerging discoveries in developmental biology have been utilized as a roadmap for driving PSCs, which resemble cells of the early embryo, into mature functional thyroid follicles in vitro. Finally, we discuss the bioengineering, biological, and clinical hurdles that now need to be addressed if the goals of life-long cure of hypothyroidism through cell- and/or gene-based therapies are to be attained.